Daily habits, diseases, drugs and knee osteoarthritis: a two-sample Mendelian randomization analysis - Zhou, Yaqiong; Wang, Qi; Chen, Liping; Bo, Yun; Zhang, Yuanyuan (Frontiers in Genetics, 2024)
The causal relationship between daily habits, diseases, drugs, and knee osteoarthritis (KOA) remains unclear. This study utilized a two-sample Mendelian randomization (MR) method to investigate the causal links between these factors and KOA, providing new insights for KOA prevention. Methods: SNPs strongly associated with exposure factors (daily habits, diseases, drugs) were extracted from publicly available genome-wide association studies (GWAS) as instrumental variables (IVs). We then selected GWAS of KOA as the outcome, conducting a two-sample MR analysis. Results: Our findings revealed significant causal relationships between several factors and KOA. There was a notable association with time spent watching TV (OR=4.038; 95% CI: 1.859-8.770; P=4.192E-04), frequency of friend/family visits (OR=0.415; 95% CI: 0.219-0.788; P=7.174E-03), smoking history (OR=0.781; 95% CI: 0.663-0.921; P=3.235E-03), gastroesophageal reflux disease (GERD) (OR=1.519; 95% CI: 1.244-1.856; P=4.183E-05), hypercholesterolemia (OR=0.498; 95% CI: 0.290-0.855; P=0.011), hypothyroidism (OR=1.048; 95% CI: 1.013-1.084; P=6.645E-03), use of antithrombotic agents (OR=0.892; 95% CI: 0.816-0.976; P=0.013), statin medication (OR=0.956; 95% CI: 0.916-0.998; P=0.041), and thyroid preparations (OR=1.042; 95% CI: 1.014-1.071; P=2.974E-03) with KOA.Specifically, KOA was positively associated with longer time spent watching TV, GERD, hypothyroidism and thyroid preparations, however showed a negative correlation with more frequent visits from friends or family, smoking history, hypercholesterolemia, antithrombotic agents and statin medication. Sensitivity analysis indicated no significant pleiotropy in these studies (P>0.05).This comprehensive study underscores the significance of modifying certain habits to mitigate the risk of KOA. Additionally, the elevated risk of KOA among individuals with GERD, hypothyroidism, and those using thyroid preparations warrants attention.